Predictors of survival after emergency department thoracotomy in trauma patients with predominant thoracic injuries in Southern Israel: a retrospective survey - Refaely, Yael (Open Access Emerg Med, 2019)
Introduction: Emergency department thoracotomy (EDT), also termed “resuscitative thoracotomy”, is indicated in some cases of life-threatening isolated thoracic injury, or as a part of CPR (cardiopulmonary resuscitation) in multiple trauma patients, or in thoracic trauma patients with massive bleeding (such as intra-abdominal exsanguination or injury to the great vessels). There is a lack of information in the literature concerning predictors of survival after EDT in patients with predominant or isolated thoracic trauma. Patients and methods: The study was retrospective and single-center. We collected clinical and laboratory data from all civil and military trauma patients admitted to our emergency department (ED) with predominant thoracic injuries who underwent EDT at Soroka Medical Center. A total of 31 patients were included in the study. Results: Of the patients in the study group, 58% presented with penetrating thoracic injuries and 42% presented with blunt thoracic injuries. 13 patients (42%) survived the EDT procedure. The following parameters predicted survival after EDT: signs of life and the presence of sinus rhythm on admission to the ED; heart rate at the end of the EDT procedure; short duration of EDT; and total positive balance (fluid and blood products) after EDT. Patients who sustained penetrating stab wound injuries had a better immediate post-operative survival rate after EDT than those who sustained penetrating gunshot wounds or predominant blunt chest trauma (30.8% vs 11.1%; p-0.034). Six patients (19%) survived until discharge from the hospital: 3 with penetrating injuries and 3 with blunt thoracic injuries. Conclusion: In patients undergoing EDT after thoracic injury we found that the clinical status on admission to the ED, the duration of the EDT procedure and the heart rate at the end of procedure were predictors of survival after EDT. We demonstrated a higher survival rate after EDT in patients with predominant penetrating thoracic trauma.